PREVENTION OF INFECTIONS ASSOCIATED WITH THE PROVISION OF MEDICAL CARE IN PATIENTS WITH CYSTIC FIBROSIS IN A MULTIDISCIPLINARY HOSPITAL IN KUZBASS FOR THE PERIOD 2020-2021 - Михаил Исаакович Ликстанов; Светлана Анатольевна Кузьменко; Вадим Гельевич Мозес; Светлана Николаевна Мовшина; Екатерина Валерьевна Баринова; Оксана Владимировна Коваливнич; Денис Иванович Балагуш; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес (Медицина в Кузбассе, 2022)
A descriptive retrospective continuous epidemiological study of cases of bacterial isolation in pediatric patients (from 1 to 15 years of age) was performed in the regional center of cystic fibrosis, GAUZ KOKB named after S.V. Belyaev. A total of 64 case histories of an inpatient with a diagnosis of cystic fibrosis and the results of microbiological studies over a two-year period were studied. Patients with this nosology are predisposed to the colonization of the respiratory tract by various microorganisms, which aggravates the course of the disease. The system of anti-epidemic, preventive measures in the hospital allows you to avoid infection of patients during their stay.